2010
DOI: 10.1038/nchem.728
|View full text |Cite
|
Sign up to set email alerts
|

The role of steps in surface catalysis and reaction oscillations

Abstract: Atomic steps at the surface of a catalyst play an important role in heterogeneous catalysis, for example as special sites with increased catalytic activity. Exposure to reactants can cause entirely new structures to form at the catalyst surface, and these may dramatically influence the reaction by 'poisoning' it or by acting as the catalytically active phase. For example, thin metal oxide films have been identified as highly active structures that form spontaneously on metal surfaces during the catalytic oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
175
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 27 publications
11
175
3
1
Order By: Relevance
“…However, some studies also indicate Pd surfaces covered 37 by atomic oxygen as highly active [8,17], and generally both will exhibit activity. For Pd(100), the 38 presence of a (√5x√5)R27° surface oxide (henceforth denoted √5) is found to exist when the surface 39 is highly active towards CO oxidation [5,6,8,10,14,17,18], and this is consistent with the reaction 40 following a Mars-van Krevelen mechanism with gas-phase CO reacting with the surface oxide to 41 form CO2 [5][6][7]9,11,[13][14][15]19]. The presence of the surface oxide during high CO2 production is also 42 supported by kinetic Monte-Carlo simulations [20,21].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, some studies also indicate Pd surfaces covered 37 by atomic oxygen as highly active [8,17], and generally both will exhibit activity. For Pd(100), the 38 presence of a (√5x√5)R27° surface oxide (henceforth denoted √5) is found to exist when the surface 39 is highly active towards CO oxidation [5,6,8,10,14,17,18], and this is consistent with the reaction 40 following a Mars-van Krevelen mechanism with gas-phase CO reacting with the surface oxide to 41 form CO2 [5][6][7]9,11,[13][14][15]19]. The presence of the surface oxide during high CO2 production is also 42 supported by kinetic Monte-Carlo simulations [20,21].…”
Section: Introductionsupporting
confidence: 55%
“…Surface oxides rather than surfaces covered by chemisorbed oxygen have been 35 observed as the most active towards CO oxidation under near ambient as well as more realistic 36 conditions (above ambient pressure) [5][6][7][8][9][10][11][12][13][14][15][16]. However, some studies also indicate Pd surfaces covered 37 by atomic oxygen as highly active [8,17], and generally both will exhibit activity.…”
Section: Introductionmentioning
confidence: 97%
“…Hendriksen et al [72], who proposes that formation and annealing of surface atomic steps is a driving force for the reduction-oxidation of palladium during oscillations in the oxidation of CO at near atmospheric pressure. Using operando X-ray diffraction technique, they identify the processes of smoothening of the metal surface and roughening of the oxide surface during inactive and active half-periods of the oscillations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…the surface oxide is catalytically more active. Later, the same group using HP-SXRD observed the formation of thin surface oxide in the highly reactive region and claimed the interaction between the surface oxide and surface steps was the origin of the oscillatory behavior in CO oxidation at elevated pressure conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…e.g. high-pressure SPM [5], ambient pressure x-ray photoemission spectroscopy (AP-XPS) [6], polarization modulation infrared reflection absorption spectroscopy (PM-IRAS) [7], and high-pressure surface x-ray diffraction (HP-SXRD) [8,9]. These in situ operando techniques have delivered numerous intriguing results and shown that the surface reaction under highpres sure conditions can be different from those under UHV conditions [5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%